2015
DOI: 10.1002/dc.23391
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cervical cytology with high‐risk HPV molecular diagnosis, genotypes, and histopathology—A four year study from the UAE

Abstract: Assessment of cervical cytology reporting pattern, correlation of cervical cytology with HPV molecular diagnosis, and biopsy histopathology is a useful way to audit our work and a good quality control practice. Higher prevalence of HPV HR types such as type 51, 31 as well as 66, 56, and 59 found in the present as well as many similar other studies apart from the commonest subtype 16 may imply necessity for development of more targeted and multivalent anti-HPV vaccines for protection of women in our region. HPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
1
9
1
3
Order By: Relevance
“…In addition, a subsequent meta‐analysis of women with normal cytological findings found that the adjusted HPV prevalence was 11.7%, although it varies geographically . Furthermore, previous studies in some GCC countries reported HPV prevalence ranging from 2.36% to 60.7% among women with normal cytology, whereas, among women with abnormal cytology, the HPV positivity rate ranged from 16.7% to 64.6% . The high prevalence of HR‐HPV among women with normal cytology in our study could be explained by the low sensitivity of the Papanicolaou test.…”
Section: Discussioncontrasting
confidence: 42%
See 1 more Smart Citation
“…In addition, a subsequent meta‐analysis of women with normal cytological findings found that the adjusted HPV prevalence was 11.7%, although it varies geographically . Furthermore, previous studies in some GCC countries reported HPV prevalence ranging from 2.36% to 60.7% among women with normal cytology, whereas, among women with abnormal cytology, the HPV positivity rate ranged from 16.7% to 64.6% . The high prevalence of HR‐HPV among women with normal cytology in our study could be explained by the low sensitivity of the Papanicolaou test.…”
Section: Discussioncontrasting
confidence: 42%
“…Conversely, the frequency of HPV16 and HPV18 double infections was 1%. In the GCC countries, although the majority of investigations found that HPV16 was the most commonly identified HR‐HPV genotype, other studies reported other non‐HPV16 HR‐HPV as the most frequently detected genotype …”
Section: Discussionmentioning
confidence: 98%
“…Since the HPV vaccine distributed in the national program is a quadrivalent that offers protection against these two high-risk types, knowing this information can help towards developing and adopting more comprehensive vaccines in our country [37]. The frequency of this genotype distribution is quite similar to that found in another Cobas PCR study for ASC-US [38].…”
Section: Discussionsupporting
confidence: 58%
“…Another interesting finding of this study is a higher prevalence of other HR-HPV genotypes compared to HPV-16 and -18 genotypes, which are the most frequent HR-HPVs detected in other studies and more linked to squamous cell cancer [36, 37]. Since the HPV vaccine distributed in the national program is a quadrivalent that offers protection against these two high-risk types, knowing this information can help towards developing and adopting more comprehensive vaccines in our country [37].…”
Section: Discussionmentioning
confidence: 67%
“…The findings are in keeping with the current report showing hrHPV 18 as a less frequent hrHPV type in the UAE population [ 28 ]. Similarly, Krishnan and Thomas reported HPV 16 to be the most common HPV type in cases with abnormal Pap smear [ 29 ]. Likewise, hrHPV 18 was not the second most frequent type.…”
Section: Discussionmentioning
confidence: 99%